A Randomized in situ Clinical Study of Fluoride Dentifrices on Enamel Remineralization and Resistance to Demineralization: Effects of Zinc - Creeth, Jonathan E; Karwal, Ritu; Hara, Anderson T; Zero, Domenick T (Caries research, 2018)
This study aimed to determine the effect of zinc ions and F concentration in a dentifrice on remineralization of early caries lesions in situ and on resistance to subsequent demineralization. This was a single-center, 6-period, 6-product, blinded (examiner, subject, analyst), randomized (n = 62), crossover study. Products (all NaF) were: 0, 250, 1,150 and 1,426 ppm F (dose-response controls), "Zn-A" (0.3% ZnCl2, 1,426 ppm F), and "Zn-B" (as Zn-A, with high-foaming surfactants) in a conventional silica base. Subjects wore palatal appliances holding partially demineralized bovine enamel specimens. They brushed their teeth with 1.5 g test dentifrice (25 s), then swished the slurry ensuring even exposure of specimens (95 s), expectorated, and rinsed (15 mL water, 10 s). After 4 h intraoral remineralization, specimens were removed and acid-challenged in vitro. Surface microhardness (SMH), measured pre-experimental, post-initial acid exposure, post-remineralization, and post-second acid exposure, was used to calculate recovery (SMHR), net acid resistance (NAR), and a new, specifically demineralization-focused calculation, "comparative acid resistance" (CAR). Enamel fluoride uptake (EFU) was also measured. For the F dose-response controls, all measures showed significant relationships with dentifrice F concentration (p < 0.0001). The presence of zinc counteracted the ability of F to promote remineralization in this model. Compared to the 1,426 ppm F control, the zinc formulations gave reduced SMHR, EFU, and NAR (all p < 0.0001); however, they showed evidence of increased CAR (Zn-A: p = 0.0040; Zn-B: p = 0.0846). Products were generally well tolerated. In this study, increasing dentifrice F concentration progressively increased in situ remineralization and demineralization resistance of early caries enamel lesions. Zinc ions reduced remineralization but could increase demineralization resistance.